EFFECTS OF ENTREPRENEURIAL ORIENTATION AND DYNAMIC CAPABILITIES ON ORGANISATIONAL PERFORMANCE OF LOGISTICS SERVICE PROVIDERS IN MALAYSIA - Lee, Sherlene; Poh, Phaik See (INTI International University, 2023)
Often, when organisations encounter abrupt and persistent changes within business environment - firms’ entrepreneurial orientation and dynamic capabilities were poised as the pivotal point in rendering firms’ success or failure. The effects of three entrepreneurial oriented insights – proactiveness, risk-taking and innovativeness upon organisational performance have been constantly studied over decades but is indeed, a rare gem in logistics. Intense competition pushes industry players to work in isolation with minimal sharing thus hinder desired progression. Retailers and high-tech giants developed in-house logistics, aspiring for market expansion by acquisition of existing logistics service providers, which, eventually, switched role from customers to competitors. Surpassed by ASEAN peers in Logistics Performance Index, Malaysia’s position declined from 32nd to 41st (2016-2018), thereby, an obvious slack in Logistics Service Quality (The World Bank, 2018). From within, logistics hiccups in comprehending manpower shortage, technology know-how, costing, geographical coverage, operational complications. Yet, industrywide, they are facing port and depot congestion, hijacking threats, customs complications, and environmental absurdities, triggering the need for cost efficiency and service delivery effectiveness. Thereby, the study aims to explore the effects of entrepreneurial orientation as in proactiveness, risk-taking, and innovativeness, including the mediating role of dynamic capabilities as in sensing, seizing, and reconfiguring upon organisational performance. Tweaking to collect from 282 respondents only from founders, owners, general managers, and senior executives, working in logistics firms, the data were analysed using Smart PLS and SPSS. Findings show significance of “Risk-Taking” and “Innovativeness” which unleashes insights for the industry to grasp opportunities and incorporate innovativeness to accomplish desired organisational performance. Ultimately, adopting an entrepreneurial stance stimulates a promising outlook for the nation’s logistics industry players in overall. Besides, dynamic capabilities in sensing, seizing, and reconfiguring snapped up a strong mediating role in sparkling organisational performance. As such, in contrast to the perception by most industry players that the anticipatory initiatives are trivial, the findings revealed otherwise. Previous literatures on the influence of entrepreneurial initiatives of boldness and ingenuity to drive logistics firms’ performance is, thus affirmed. Moving forward, relevant stakeholders could maximise both extrinsic and intrinsic organisational values by acknowledging the cruciality of entrepreneurial orientation and dynamic capabilities in logistics service providers’ business performance, development, and industrial competencies in years to come.